Theorizing the Emergence of Change in Daily Living: Developing a Contextual Framework for Social Work Practice. - Keenan, Elizabeth King (2008)
Keywords: dept.swk; faculty_collection; sabbatical_report

Social work practice with LGBT people within organizations - Appleby, G.A.; Colon, E. (Soc. Work Pract. with Lesbian Gay Bisexual and Transgender People: Second Ed., 2008)
Journal Abbreviation: Soc. Work Pract. with Lesbian Gay Bisexual and Transgender People: Second Ed.
Keywords: dept.swk

Third Space Activities and Change Processes: An Exploration of Ideas from Social and Psychodynamic Theories. - Keenan, Elizabeth; Miehls, Dennis (Clinical Social Work Journal, 2008)
Discussions pertaining to culture, power and/or identity frequently create tensions that are enacted by dyads and groups within schools, workplaces and communities. Although tensions can easily escalate into conflict or violence, we have observed that these tensions can serve as prompts that promote a change process. When individual perspectives are challenged, some participants are able to dissemble their views and consider other perspectives from which new understandings and views emerge. At times, when groups seem to be on the threshold of overt conflict, some participants engage in processes that examine the tension, explore new possibilities, and alter the view of one's subjectivity. We suggest that these activities occur as momentary states in psychological spaces conceptualized as third spaces (Bhabha, The location of culture. London: Routledge, 1994). In this paper, we use concepts from psychodynamic and social theories to describe the conditions that coalesce to form states of mind (nepantla) (Anzaldua, Borderlands/La Frontera: The new mestiza. San Francisco: Aunt Lute Books, 1999; Interviews Entrevistas. New York: Routledge, 2000) and the ability to engage in new relational possibilities (third space activities) with dyads and groups, outside of psychotherapy. The conditions include: critical consciousness, regulation, recognition, and responsibility. We then describe how such momentary experiences can subsequently result in an examination of one's subjectivity, particularly as it pertains to issues regarding culture, power, and identity. Throughout the paper we provide four examples from various settings to illustrate these concepts and processes. Given the increasing racial/ethnic diversity of clients and clinical social workers in North America, this concept of third spaces holds particular relevance for contemporary clinical social work practice., (C)2008 Kluwer Academic Publishers
10 citations (Crossref) [2023-10-31] Place: (C)2008 Kluwer Academic Publishers
Keywords: Change processes; Psychodynamic theory; Social theory; Third space activities; dept.swk